Pengaruh Lingkungan Kerja Fisik Dan Motivasi Terhadap Kinerja Pada PT Bisma Narendra Di Cibitung Kabupaten Bekasi - Tania Zahara Ramadhani; Abu Bakar Dja’far (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of physical work environment and motivation on employee performance at PT Bisma Narendra in Cibitung, Bekasi Regency. The method used is quantitative with a causal associative approach.. The sampling technique used saturated sampling, namely 84 respondents. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are the physical work environment has a significant effect on employee performance with a coefficient of determination of 39.6% and hypothesis testing obtained t count> t table or 7.333> 1.989. Motivation has a significant effect on employee performance with a coefficient of determination of 51.8% and hypothesis testing obtained t count> t table or (9,392> 1,989). The physical work environment and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 7.926 + 0.310X1 + 0.489X2. The coefficient of determination is 58.1% while the remaining 41.9% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or 56.161> 2.720.